Assessing connectivity related injury burden in diffuse traumatic brain injury. Issue 6 (15th March 2017) - Solmaz, Berkan; Tunç, Birkan; Parker, Drew; Whyte, John; Hart, Tessa; Rabinowitz, Amanda; Rohrbach, Morgan; Kim, Junghoon; Verma, Ragini
Abstract: Many of the clinical and behavioral manifestations of traumatic brain injury (TBI) are thought to arise from disruption to the structural network of the brain due to diffuse axonal injury (DAI). However, a principled way of summarizing diffuse connectivity alterations to quantify injury burden is lacking. In this study, we developed a connectome injury score, Disruption Index of the Structural Connectome (DISC), which summarizes the cumulative effects of TBI‐induced connectivity abnormalities across the entire brain. Forty patients with moderate‐to‐severe TBI examined at 3 months postinjury and 35 uninjured healthy controls underwent magnetic resonance imaging with diffusion tensor imaging, and completed behavioral assessment including global clinical outcome measures and neuropsychological tests. TBI patients were selected to maximize the likelihood of DAI in the absence of large focal brain lesions. We found that hub‐like regions, with high betweenness centrality, were most likely to be impaired as a result of diffuse TBI. Clustering of participants revealed a subgroup of TBI patients with similar connectivity abnormality profiles who exhibited relatively poor cognitive performance. Among TBI patients, DISC was significantly correlated with post‐traumatic amnesia, verbal learning, executive function, and processing speed. Our experiments jointly demonstrated that assessing structural connectivity alterations may be useful in development of patient‐oriented diagnostic and prognostic tools. Hum Brain Mapp 38:2913–2922, 2017 . ©2017 Wiley Periodicals, Inc.